2009
DOI: 10.1007/s00264-009-0776-3
|View full text |Cite
|
Sign up to set email alerts
|

Results of the proximal femoral nail anti-rotation (PFNA) in elderly Chinese patients

Abstract: A prospective study is presented of 87 unstable intertrochanteric fractures treated with the proximal femoral nail anti-rotation (PFNA) with a follow-up of one year. Of the patients 76% were female. The average age was 75.3 years. The fracture was treated by closed reduction and intramedullary fixation. Pre-injury activity level was recovered in 77% of the patients. Fractures united in all patients. Mechanical failure and cut-out were not observed. A technical problem related to the mismatch of the proximal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 15 publications
5
84
3
Order By: Relevance
“…Postoperative reduction and position of the lag screw were normal however osteoporosis was not evaluated. Jin et al (13) reported a case series of 87 patients with no failure of fixation. Baumgaertner et al (21) in their study determined the ideal screw position and tip apex distance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative reduction and position of the lag screw were normal however osteoporosis was not evaluated. Jin et al (13) reported a case series of 87 patients with no failure of fixation. Baumgaertner et al (21) in their study determined the ideal screw position and tip apex distance.…”
Section: Discussionmentioning
confidence: 99%
“…Reported complications are cut-out, medial migration of the lag screw, perforation of the femoral head, malunion in varus position, nonunion, avascular necrosis, implant failure, neurovascular injuries and stress fracture distal to the nail. The most common complication is the cut-out of the lag screw from the femoral head in varus malunions or nonunions (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Less common complications of proximal femoral nails are pelvic or lateral migration of the lag screw and perforation of the sigmoid colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38% of patients required blood transfusion. W.M Gadegone et al 29 in their study reported that 3 patients (3%) required post operative blood transfusion.…”
Section: ) Blood Lossmentioning
confidence: 99%
“…The most widely used extramedullary implant-Dynamic Hip Screw {DHS}-seems to have a biomechanical disadvantage when compared with Intramedullary devices because the load bearing in Proximal femur is predominantly shared by the calcar. Intramedullary devices such as the Proximal femoral nail {PFN}, are more stable under loading with shorter lever arm, so the distance between hip joint & the nail is reduced compared with that of a plate, thus diminishing the deforming forces across the implant 4 major biomechanical innovations to overcome the limitations of the DHS & Gamma nail The addition of the 6.4 mm anti-rotation hip pin to reduce the incidence of implant cut-out & the rotation of the cervico-cephalic fragments The smaller diameter & fluting of the tip of the nail, specially designed to reduce stress forces below the implant & therefore the incidence of lowenergy fracture at the tip. The greater implant length, smaller valgus angle & setting of this angle at a higher level (11 cm from the proximal end) The more proximal positioning of the distal locking, to avoid abrupt changes in stiffness of the construct.…”
Section: Introductionmentioning
confidence: 99%